2014
DOI: 10.1071/mf13077
|View full text |Cite
|
Sign up to set email alerts
|

Warm-phase ENSO events modulate the continental freshwater input and the trophic state of sediments in a large South American estuary

Abstract: Abstract. We studied the changes in geochemical variables in the middle section of Río de la Plata estuary during the 2009-2010 El Niño-Southern Oscillation (ENSO) event. Protein, organic matter, chlorophyll-a and phaeopigment content of surface sediments were significantly correlated with the increased continental freshwater input associated with high total monthly rainfall. During the warm-phase ENSO event, river flow was 5-fold larger than average historical levels, which led to a steady decrease in salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
1
15
0
4
Order By: Relevance
“…Moreover, the São Gonçalo channel has a gentle slope [8], which contributes to the low water flux towards the Patos lagoon and the increase in the Mirim lagoon water levels. Oliveira et al [12] suggested that freshwater inputs for the Mirim lagoon are influenced by ENSO events, increasing the precipitation in the region [31,32]. The ENSO influence on the Mirim lagoon was also observed by [25].…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, the São Gonçalo channel has a gentle slope [8], which contributes to the low water flux towards the Patos lagoon and the increase in the Mirim lagoon water levels. Oliveira et al [12] suggested that freshwater inputs for the Mirim lagoon are influenced by ENSO events, increasing the precipitation in the region [31,32]. The ENSO influence on the Mirim lagoon was also observed by [25].…”
Section: Resultsmentioning
confidence: 85%
“…In total, 36 water samples were analysed. The system presents strong temporal and spatial gradients in terms of temperature, conductivity (which was used as a proxy of salinity) and turbidity (Acha et al, 2008;Ferrari et al, 2011;García-Rodríguez et al, 2013;Kruk et al, 2015;Martínez de la Escalera et al, 2017). The highest surface water temperatures in Salto Grande reservoir are usually recorded during summer (January to March, 19-33 °C) while the lowest temperatures belong to the outer marine zone of the Río de la Plata during winter-early spring (June to October, 11-18 °C) Martínez de la Escalera et al, 2017).…”
Section: Study Sitementioning
confidence: 99%
“…However, it is still extremely difficult to predict the intensity and scale of these changes and the response of biological communities and changes in ecosystem functioning. Temperature and rainfall anomalies, as well as sea level rise, have been commonly reported across the globe and these effects may have substantial impacts on estuarine ecosystems over both the short-and long-term (ALONGI, 2008;DAY et al, 2008;CONDIE et al, 2012;TURRA et al, 2013;GARCÍA-RODRIGUEZ ET AL., 2014). For example, if regional and local rainfall anomalies and sea level changes alter the salt balance of an estuary, it might cause changes in species distribution and productivity (THURMAN et al, 2010;CONDIE et al, 2012).…”
Section: Introductionmentioning
confidence: 99%